완전미율이 높고 숙색이 좋은 벼 ‘상보(上寶)’ - 박노봉(No-Bong Park), 여운상(Un-Sang Yeo), 이지윤(Ji-Yoon Lee), 박동수(Dong-Soo Park), 이종희(Jong-Hee Lee), 조준현(Jun-Hyun Cho), 송유천(You-Chun Song), 오성환(Seong-Hwan Oh), 손영보(Young-Bo Son), 장재기(Jae-Ki Chang) (Korean journal of breeding, 2020)
‘Sangbo’ is a japonica rice (Oryza sativa L.) variety with high head rice grain ratio and good ripened grain color, as well as resistance to rice dwarf virus (RDV) and bacterial blight disease (BB). It was developed by the rice breeding team of the Yeongdeok Branch of the National Institute of Crop Science, RDA, Korea, in 2015. This variety was derived in the 2002 summer season from a cross between ‘Yeongdeog32’, with high eating quality, and ‘Nampyeong’, with a high milling ratio. In 2012, a promising line, YR24256-142-5-3-1-1-2, selected by the pedigree breeding method, was designated the name, ‘Yeongdeog59’. After performing a local adaptability test at nine locations from 2013 to 2015, ‘Yeongdeog59’ was released with the name ‘Sangbo’ in 2015. ‘Sangbo’ has a culm length of 77 cm and a medium-late growth duration. This variety was resistant to K1, K2, and K3 races of bacterial blight, along with the dwarf virus, and was moderately resistant to leaf blast disease. Based on the results of a panel test, ‘Sangbo’ has translucent and clear milled rice kernel without white core and belly rice, and good eating quality. The yield potential of ‘Sangbo’ in milled rice was approximately 6.21 MT/ha at the ordinary fertilizer level of the local adaptability test (LAT). This cultivar would be adaptable to the middle plain, south plain, Yeongnam plain, east coastal area, and south mid-mountainous areas of Korea (Registration No. 7284, 2018.06.25). KCI Citation Count: 0